1993
DOI: 10.1002/ar.1092360315
|View full text |Cite
|
Sign up to set email alerts
|

Development of innervation of skeletal muscle fibers in man: Relation to acetylcholine receptors

Abstract: The aim of this study was to establish the time scale of developmental changes in innervation of skeletal muscle fibers in man. Specimens of thigh and intercostal muscle from 19 embryos and 18 infants were examined with histological methods which enabled the discrimination between fetal (gamma) and adult (epsilon) types of acetylcholine receptors (AChRs). At 8 weeks of development, AChRs were distributed diffusely in the myotube membranes. Following onset of innervation in approximately the ninth week the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 41 publications
2
80
0
2
Order By: Relevance
“…The measured data of MEP lengths from 18-27 µm (Namba et al, 1968;Wokke et al, 1990;Hesselmans et al, 1993) are in accordance with the evaluated facial MEP lengths of 25-27 µm.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The measured data of MEP lengths from 18-27 µm (Namba et al, 1968;Wokke et al, 1990;Hesselmans et al, 1993) are in accordance with the evaluated facial MEP lengths of 25-27 µm.…”
Section: Discussionmentioning
confidence: 84%
“…Former studies by other authors concerning the innervation of human skeletal muscles (Desmedt, 1958;Christensen, 1959;Schwarzacher, 1959;Aquilonius et al, 1984;Carlson, 1986;Wokke et al, 1990;Hesselmans et al, 1993) have shown that focal innervation of muscle fibers with one MEP is the predominant type. We conclude that multifocally innervated fibers would have been found by these authors if present.…”
Section: Discussionmentioning
confidence: 96%
“…Together, these subunits form a cationspecific ion channel that opens when ACh binds to the two sites at the ␣/␦ and either the ␣/␥ or ␣/⑀ interfaces (Unwin, 2000). From about 30 weeks of gestation in humans, the "adult"-specific ⑀ subunit gradually replaces the ␥ subunit (Hesselmans et al, 1993), but the fetal isoform continues to be expressed on rare myoid cells in the adult thymic medulla .…”
mentioning
confidence: 99%
“…Speech and nonspeech activities in such a case would be expected to demonstrate similar levels of coupling of upper and lower lip activity, as lip muscle activation patterns would be similar in timing and amplitude. Two-year-old children were chosen for this study, because, at this age: (a) the CNS (e.g., Hesselmans, Jennekens, van den Oord, Veldman, & Vincent, 1993;Simonds & Scheibel, 1989) and oral and facial structures (Moyers & Carlson, 1990) are not yet fully developed, (b) essential investigations of physiologic development of speech motor control are lacking, and (c) most 2-year-olds are able to follow a minimally constrained experimental protocol. Observation of freely behaving children this young presents several challenges.…”
mentioning
confidence: 99%